Transcriptional changes in the rat brain induced by repetitive transcranial magnetic stimulation - Weiler, Marina; Stieger, Kevin C.; Shroff, Kavisha; Klein, Jessie P.; Wood, William H.; Zhang, Yongqing; Chandrasekaran, Prabha; Lehrmann, Elin; Camandola, Simonetta; Long, Jeffrey M.; Mattson, Mark P.; Becker, Kevin G.; et al. (Frontiers in Human Neuroscience, 2023)
Repetitive transcranial magnetic stimulation (rTMS) has emerged as a promising tool to treat neuropsychiatric conditions, but the molecular changes it causes in brain are largely unknown. In this study, using three experimental models in rats, we report that the effects of rTMS are more complex and dynamic than previously known. Specifically, alterations in gene expression are dependent on brain region, stimulation protocol, age, and interval after treatment. Among the clinically relevant rTMS-induced alterations found here, we highlight expression changes in genes involved in glutamatergic, GABAergic, and inflammatory pathways. Importantly, rTMS affected the expression of genes involved in disorders for which it is being tested clinically, including Alzheimer's and Parkinson's disease. Our findings provide a foundation for future research that aims to tailor rTMS for the treatment of neuropsychiatric conditions.